Community surveillance of Aedes albopictus associated with Wolbachia detection in low-rise residential areas in Selangor, Malaysia - Muhammad Aidil, Roslan; Romano, Ngui; Indra, Vythilingam; Wan Yusoff, Wan Sulaiman (2022)
The study assessed the distribution of Malaysian Ae. albopictus adults associated with Wolbachia detection in low-rise residential areas using a modified sticky ovitrap (MSO). The relationship between Ae. albopictus and climatological parameters were also determined. Fifty-two weeks of surveillance using 273 MSOs were conducted in four installation areas of eleven sampling sites. Specimens were subjected to PCR using wsp-specific primers for Wolbachia detection. The relationship between climatological parameters and Ae. albopictus captured were analyzed using Spearman rank correlation coefficient test. The majority of Ae. albopictus were captured in residential houses (87%), followed by playgrounds or parks (11.5%), guardhouses (1%), and community halls (0.5%). Most of the specimens (92%) were superinfected with wAlbA and wAlbB strains. A positive correlation with no significant association was found for rainfall (r = 0.015, P = 0.072), relative humidity (r = 0.005, P = 0.526), minimum temperature (r = 0.005, P = 0.516), and mean temperature (r = 0.003, P = 0.689). MSO effectively captured a high number of Ae. albopictus that was determined to be the predominant mosquito species found in low-rise residential areas. The adult collection is not only influenced by climatological parameters but also by other factors, including environmental conditions and general sanitation status.